Café conilon (Coffea canephora Pierre ex Froehner) processado por via natural com inoculação de leveduras - Silva, Bruna Lessa da (2019)
There are several factors that can affect the sensory quality of coffee, among them are the altitude of cultivation, the forms of processing and the action of microorganisms. In this context, yeast can be used as starter cultures to generate important flavor precursors. Two yeasts were inoculated during the natural drying of conilon coffee. Microbial group counts were performed by plating. Yeast follow-up during fermentation was performed by real-time PCR. Organic acids and sugars were quantified by HPLC. Volatile compounds were identified by gas chromatography. The cup test with six tasters and triangular test was performed. Inoculation significantly influenced the populations of lactic acid bacteria and fungi. For the latter, inoculation with M. guilliermondii at an altitude of 600 m was able to reduce the final population in a log cycle. P. kluyveri count was higher for samples inoculated with this yeast. Twenty-four volatile compounds were identified and their profile was influenced by altitude and yeast inoculation. Acetic, lactic, malic, oxalic and propionic acids were identified during all analysis times. Sugars decreased in concentration during drying. The inoculation of M. guilliermondii and P. kluyveri in coffees from 300 m altitude was able to increase the overall grade of the samples, while for the 600 m altitude there was a drop in this with inoculation. In the triangular test it was possible to detect significant difference only for the sample fermented with M. guilliermondii at an altitude of 600 m. The present study concluded that yeast inoculation may be advantageous depending on the coffee cultivation altitude.